Does Digital Leadership Improve Employee Performance? A Meta-Analytic and Bibliometric Evidence from Public Sector Studies - Orlibernawati Orlibernawati; Shalahuddin Shalahuddin; Tinik Sugiati (Amkop Management Accounting Review (AMAR), 2026)
Digital transformation has fundamentally reshaped organizational leadership practices, positioning digital leadership as a critical determinant of employee performance. Although the literature on digital leadership has expanded rapidly, empirical findings regarding its impact on employee performance remain varied and have not been systematically integrated, particularly within the public sector context. This study aims to comprehensively examine the relationship between digital leadership and employee performance using a meta-analytic and bibliometric approach based on Scopus-indexed articles published between 2021 and 2025. The meta-analysis estimates the overall effect size of digital leadership on employee performance, while the bibliometric analysis maps publication trends, intellectual structures, and dominant research themes. The findings indicate that digital leadership has a positive and significant effect on employee performance and is increasingly positioned as a contemporary leadership paradigm integrating strategy, technology, and organizational behavior. These results highlight the importance of strengthening leaders’ digital competencies to enhance employee effectiveness and productivity in technology-driven organizational environments. This study contributes theoretically by integrating empirical evidence with intellectual structure mapping and provides practical implications for the development of digital leadership, particularly in the public sector.